Meningkatkan Mutu pendidikan Melalui Kegiatan Bimbingan Belajar Gratis di Desa Tahai Jaya Kecamatan Maliku Kabupaten Pulang Pisau, Kalimantan Tengah - Muhammad Imam Santoso; Norlela Norlela; Beti Setiawati; Eka Wahyuni; Mirna Lestari; Nur Aisah; Nurul Ramadani (Lembaga Pengembangan Kinerja Dosen, 2024)
Education standards in Indonesia still face various challenges, especially in Tahai Jaya Village where there are still educational problems such as limited Merdeka curriculum books, unstable lesson schedules, and the low reading ability of grade 3 elementary school students, reflecting broader educational challenges. To overcome this, KKN students took the initiative to carry out free tutoring in Tahai Jaya village. The aim of this free tutoring program is to help improve the quality of education in Tahai Jaya village. The method used is the PAR (Participatory Action Research) method. The results of free tutoring activities in Tahai Jaya Village have succeeded in improving the quality of education in the area. This activity involves active community participation and is carried out for a month using interactive methods. As a result, students show increased motivation and learning abilities, especially in completing school assignments. Parents also felt the positive impact of this activity, because their children were more enthusiastic and eager to learn.